Dinamika podjetniškega potenciala: GEM Slovenija 2016 - Rebernik, Miroslav; Crnogaj, Katja; Širec, Karin; Bradač Hojnik, Barbara; Rus, Matej; Tominc, Polona (University of Maribor Press, 2017)
Dynamics of Entrepreneurial Potential : GEM Slovenia 2016. The book presents the results of the largest longitudinal study of entrepreneurship in the world, the Global Entrepreneurship Monitor. It is based on data collected in 2016 and before, and deals with the interconnectedness of entrepreneurship and economic development. This monograph brings the results of the study of entrepreneurship in Slovenia and compares them with the results of other countries. It is based on a joint methodology and performed within a closely linked and interconnected global network of researchers, allowing detailed international comparisons. The book enables a better understanding of societal values about entrepreneurship and the specific individual characteristics of persons, such as their perception of their own entrepreneurial capabilities, their ability to perceive business opportunities, their entrepreneurial intentions and their fear of failure. Because the survey monitored entrepreneurial activity in all phases of the life cycle (nascent, new and established businesses, business discontinuation), and according to the impact and type of activity, it delivers a comprehensive picture of entrepreneurship processes and their ecosystem. A substantial amount of attention is also devoted to entrepreneurial aspirations and the quality of the entrepreneurship ecosystem, since the latter may significantly foster (or constrain) entrepreneurial processes in a society.